Pengaruh Akses Sanitasi Layak, Kemiskinan dan Jumlah Penduduk Terhadap IKLH di Pulau Sumatera Tahun 2018-2022 - Falatansya, Syafira; Sabrina, Sukma Amalia; Wulandari, Puspa; Permana, Elang; Purwoto, Agus (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the influence of access to proper sanitation, poverty, and population on the Environmental Quality Index (IKLH) on Sumatra Island during the period 2018–2022. Environmental problems in this region are influenced by socio-economic and demographic factors, such as low access to sanitation, poverty levels, and uneven population growth. The study uses a quantitative approach with a Fixed Effect Model panel data regression model, selected based on the results of the Chow and Hausman test. Data used are sourced from the Central Statistics Agency (BPS), processed to produce a picture of fluctuations in the IKLH, sanitation access, poverty, and population in ten provinces on Sumatra Island. The results show that access to proper sanitation has a positive effect on the IKLH, while poverty and population have a negative effect. Aceh Province recorded the highest IKLH, while Lampung recorded the lowest, with variations influenced by infrastructure and welfare inequality. The output of this study is expected to form the basis for policies to improve environmental quality through improving sanitation access, poverty alleviation, and managing sustainable population growth.